Species-Specific Recognition in Fig-Wasp Mutualism: The Role of Volatile Blends and Seasonal Shifts in Olfactory Responses - Niannian Liang; Benoit Lapeyre; Ramil Kohkaew; Yongxia Jia; Magali Proffit; Hui Yu (Journal of Chemical Ecology, 2026)

Effects of ubiquitous plasticizers on olfactory perception in the buff-tailed bumble bee - Marion Javal; Maryse Vanderplanck; Thibaut Bachelet; Marie Dolfi; Juliette Fernandes; Benoit Lapeyre; Lilian Roux; Virginie Cuvillier; Magali Proffit (Ecotoxicology, 2026)

Ozone alters the chemical signal required for plant – insect pollination: The case of the Mediterranean fig tree and its specific pollinator - Candice Dubuisson; Henri Wortham; Tessie Garinie; Martine Hossaert-McKey; Benoit Lapeyre; Bruno Buatois; Brice Temime-Roussel; Elena Ormeño; Michael Staudt; Magali Proffit (Science of The Total Environment, 2024)

Ozone exposure induces metabolic stress and olfactory memory disturbance in honey bees. - Fabien Démares; Laëtitia Gibert; Benoit Lapeyre; Pierre Creusot; David Renault; Magali Proffit (Chemosphere, 2024)

Plants are the drivers of geographic variation of floral odours in brood site pollination mutualisms: A case study of Ficus hirta - Xiaoxia Deng; Bruno Buatois; Yan-Qiong Peng; Hui Yu; Yufen Cheng; Xuejun Ge; Magali Proffit; Finn Kjellberg (Acta Oecologica, 2023)

Mangrove's species are weak isoprenoid emitters - Catherine Fernandez; Amélie Saunier; Henri Wortham; Elena Ormeño; Magali Proffit; Caroline Lecareux; Stéphane Greff; Dao Van Tan; Mai Sy Tuan; Huynh Duc Hoan; Kiet Bui Nguyen The; Dounia Dhaou; et al. (Estuarine, Coastal and Shelf Science, 2023)

Molecular phylogenetic analysis and taxonomic reconsideration of Ceropegia hirsuta (Apocynaceae, Asclepiadoideae) reveal a novelty in Thailand, Ceropegia citrina sp. nov., with notes on its pollination ecology - Aroonrat Kidyoo; Manit Kidyoo; Rumsaïs Blatrix; Gwenaëlle Deconninck; Doyle McKey; Paweena Ekkaphan; Magali Proffit (Plant Systematics and Evolution, 2021)

With or without you: Effects of the concurrent range expansion of an herbivore and its natural enemy on native species interactions - David Carrasco; Gaylord A. Desurmont; Diane Laplanche; Magali Proffit; Rieta Gols; Paul G. Becher; Mattias C. Larsson; Ted C. J. Turlings; Peter Anderson (Global Change Biology, 2018)
Global climatic changes may lead to the arrival of multiple range‐expanding species from different trophic levels into new habitats, either simultaneously or in quick succession, potentially causing the introduction of manifold novel interactions into native food webs. Unraveling the complex biotic interactions between native and range‐expanding species is critical to understand the impact of climate change on community ecology, but experimental evidence is lacking. In a series of laboratory experiments that simulated direct and indirect species interactions, we investigated the effects of the concurrent arrival of a range‐expanding insect herbivore in Europe, Spodoptera littoralis , and its associated parasitoid Microplitis rufiventris , on the native herbivore Mamestra brassicae , and its associated parasitoid Microplitis mediator , when co‐occurring on a native plant, Brassica rapa . Overall, direct interactions between the herbivores were beneficial for the exotic herbivore (higher pupal weight than the native herbivore), and negative for the native herbivore (higher mortality than the exotic herbivore). At the third trophic level, both parasitoids were unable to parasitize the herbivore they did not coexist with, but the presence of the exotic parasitoid still negatively affected the native herbivore (increased mortality) and the native parasitoid (decreased parasitism rate), through failed parasitism attempts and interference effects. Our results suggest different interaction scenarios depending on whether S. littoralis and its parasitoid arrive to the native tritrophic system separately or concurrently, as the negative effects associated with the presence of the parasitoid were dependent on the presence of the exotic herbivore. These findings illustrate the complexity and interconnectedness of multitrophic changes resulting from concurrent species arrival to new environments, and the need for integrating the ecological effects of such arrivals into the general theoretical framework of global invasion patterns driven by climatic change.

Tracking the elusive history of diversification in plant–herbivorous insect–parasitoid food webs: insights from figs and fig wasps - Finn Kjellberg; Magali Proffit (Molecular Ecology, 2016)
The food webs consisting of plants, herbivorous insects and their insect parasitoids are a major component of terrestrial biodiversity. They play a central role in the functioning of all terrestrial ecosystems, and the number of species involved is mind‐blowing (Nyman et al . ). Nevertheless, our understanding of the evolutionary and ecological determinants of their diversity is still in its infancy. In this issue of Molecular Ecology, Sutton et al . ( ) open a window into the comparative analysis of spatial genetic structuring in a set of comparable multitrophic models, involving highly species‐specific interactions: figs and fig wasps. This is the first study to compare genetic structure using population genetics tools in a fig‐pollinating wasp ( Pleistodontes imperialis sp1) and its main parasitoid ( Sycoscapter sp.A). The fig‐pollinating wasp has a discontinuous spatial distribution that correlates with genetic differentiation, while the parasitoid bridges the discontinuity by parasitizing other pollinator species on the same host fig tree and presents basically no spatial genetic structure. The full implications of these results for our general understanding of plant–herbivorous insect–insect parasitoids diversification become apparent when envisioned within the framework of recent advances in fig and fig wasp biology.

‘Do you remember the first time?’ Host plant preference in a moth is modulated by experiences during larval feeding and adult mating - Magali Proffit; Mohammed A. Khallaf; David Carrasco; Mattias C. Larsson; Peter Anderson (Ecology Letters, 2015)
In insects, like in other animals, experience‐based modulation of preference, a form of phenotypic plasticity, is common in heterogeneous environments. However, the role of multiple fitness‐relevant experiences on insect preference remains largely unexplored. For the multivoltine polyphagous moth Spodoptera littoralis we investigated effects of larval and adult experiences on subsequent reproductive behaviours. We demonstrate, for the first time in male and female insects, that mating experience on a plant modulates plant preference in subsequent reproductive behaviours, whereas exposure to the plant alone or plant together with sex pheromone does not affect this preference. When including larval feeding experiences, we found that both larval rearing and adult mating experiences modulate host plant preference. These findings represent the first evidence that host plant preferences in polyphagous insects are determined by a combination of innate preferences modulated by sensory feedback triggered by multiple rewarding experiences throughout their lifetime.

Evidence for intersexual chemical mimicry in a dioecious plant - Catherine C. L. Soler; Magali Proffit; Jean‐Marie Bessière; Martine Hossaert‐McKey; Bertrand Schatz (Ecology Letters, 2012)
The dioecious Mediterranean fig, Ficus carica , displays a unique phenology in which males sometimes bloom synchronously with females (in summer), and sometimes not (in spring). Ficus carica is engaged in an obligatory mutualism with a specific pollinating wasp, which reproduces only within figs, localising them by their specific scents. We show that scents emitted by male figs show seasonal variation within individual trees. Scents of summer male figs resemble those of the co‐flowering females, and are different from those of the same male trees in spring, when female figs are absent. These differences hold even if only compounds electrophysiologically active for pollinators are considered. The similar scents of summer males and females may explain why the rewardless females are still pollinated. These results offer a tractable model for future studies of intersexual chemical mimicry in mutualistic pollination interactions.

“This is not an Apple”–Yeast Mutualism in Codling Moth - Peter Witzgall; Magali Proffit; Elzbieta Rozpedowska; Paul G. Becher; Stefanos Andreadis; Miryan Coracini; Tobias U. T. Lindblom; Lee J. Ream; Arne Hagman; Marie Bengtsson; Cletus P. Kurtzman; Jure Piskur; et al. (Journal of Chemical Ecology, 2012)

Mating Disruption of Guatemalan Potato Moth Tecia Solanivora by Attractive and Non-Attractive Pheromone Blends - Andrea Liliana Clavijo McCormick; Miriam Karlsson; Carlos Felipe Bosa Ochoa; Magali Proffit; Marie Bengtsson; Maria Victoria Zuluaga; Takehiko Fukumoto; Cam Oehlschlager; Alba Marina Cotes Prado; Peter Witzgall (Journal of Chemical Ecology, 2012)

Attraction and Oviposition of Tuta absoluta Females in Response to Tomato Leaf Volatiles - Magali Proffit; Göran Birgersson; Marie Bengtsson; Ronaldo Reis; Peter Witzgall; Eraldo Lima (Journal of Chemical Ecology, 2011)

Evidence from population genetics that the ectomycorrhizal basidiomycete Laccaria amethystina is an actual multihost symbiont - MELANIE ROY; MARIE‐PIERRE DUBOIS; MAGALI PROFFIT; LUCIE VINCENOT; ERICK DESMARAIS; MARC‐ANDRE SELOSSE (Molecular Ecology, 2008)
It is commonly assumed that ectomycorrhizal (ECM) fungi associated with temperate forest tree roots are not host‐specific. Because this assumption relies on species delineations based on fruitbodies morphology or ribosomal DNA sequences, host‐specific, cryptic biological species cannot be ruled out. To demonstrate that Laccaria amethystina has true generalist abilities, we sampled 510 fruitbodies on three French sites situated 150–450 km away from each other. At each site, populations from monospecific stands ( Abies alba , Castanea europea and Fagus sylvatica ) or mixed stands ( F. sylvatica + Quercus robur or Q. robur + Carpinus betulus ) were sampled. Three different sets of markers were used for genotyping: (i) five microsatellite loci plus the ribosomal DNA intergenic spacer, (ii) the mitochondrial large ribosomal DNA subunit, and (iii) direct amplification of length polymorphism (DALP), a new method for fungi providing dominant markers. Evidence for allogamous populations (with possible inbreeding at local scale) and possibly for biparental mitochondrial inheritance was found. All markers congruently demonstrated that L. amethystina populations show little structure at this geographical scale, indicating high gene flow (as many as 50% of founding spores in all populations being of external origin). Our results also showed that host species contributed even less to population differentiation, and there was no evidence for cryptic biological species. This first in situ demonstration of a true multihost ability in an ECM species is discussed in terms of ecology and evolutionary biology.